Coconut oil effect on the hygroscopic properties of Simalambuo wood (Lophopetalum spp.) - LIVER IMAN PUTRA ZAI; EDDYANTO EDDYANTO; NUR AZIZAH; SAHARMAN GEA; MARPONGAHTUN MARPONGAHTUN; APRI H SISWANTO (Universitas Syiah Kuala, 2022)
Simalambuo (Lophopetalum spp) trees are endemic to Southeast Asia and widely grow in the natural forests in Nias island. Local people whose experience of utilizing the simalambuo wood have claimed that the wood easily absorbs water. Throughout our searches, not many efforts to modify the physical properties of the simalambuo woods have been carried out yet. Therefore, in this study, we modified simalambuo wood by thermal treatment in coconut oil-ambient conditions. The heat treatment became an option to support the efforts in reducing the use of non-environmental-friendly materials and methods. The simalambuo wood was treated under coconut oil at 130-210oC for 6 hours. Coconut oil uptake was up to 174%, while the leaching test (AWPA E-06 standard) showed the uneasily permeate out from the wood and high retention differently in terms of treatment and cooling temperature. Heat treatment with coconut oil affected water absorption ability and improved dimensional stability of simalambuo wood. Water absorption reduced from 162% to 16%, and dimensional stability increased from 8.4% to 4.2% at 192 hours after being soaked in water. The higher the difference between treatment and cooling temperature, the better-affected water absorption ability was and the higher dimensional ability could be achieved.